Hospital Perceptions of Medicare's Sepsis Quality Reporting Initiative. Issue 12 (1st December 2017) - Barbash, Ian J.; Rak, Kimberly J.; Kuza, Courtney C.; Kahn, Jeremy M.
Abstract : BACKGROUND: In October 2015, the Centers for Medicare and Medicaid Services (CMS) implemented the Sepsis CMS Core Measure (SEP‐1) program, requiring hospitals to report data on the quality of care for their patients with sepsis. OBJECTIVE: We sought to understand hospital perceptions of and responses to the SEP‐1 program. DESIGN: A thematic content analysis of semistructured interviews with hospital quality officials. SETTING: A stratified random sample of short‐stay, nonfederal, general acute care hospitals in the United States. SUBJECTS: Hospital quality officers, including nurses and physicians. INTERVENTION: None. MEASUREMENTS: We completed 29 interviews before reaching content saturation. RESULTS: Hospitals reported a variety of actions in response to SEP‐1, including new efforts to collect data, improve sepsis diagnosis and treatment, and manage clinicians' attitudes toward SEP‐1. These efforts frequently required dedicated resources to meet the program's requirements for treatment and documentation, which were thought to be complex and not consistently linked to patient‐centered outcomes. Most respondents felt that SEP‐1 was likely to improve sepsis outcomes. At the same time, they described specific changes that could improve its effectiveness, including allowing hospitals to focus on the treatment processes most directly associated with improved patient outcomes and better aligning the measure's sepsis definitions with current clinical definitions. CONCLUSIONS: Hospitals are responding to the SEP‐1 program across a number of domains and in ways that consistently require dedicated resources. Hospitals are interested in further revisions to the program to alleviate the burden of the reporting requirements and help them optimize the effectiveness of their investments in quality‐improvement efforts.